Towards Verification of UML Class Models using Formal Specification Methods: A Review (Global Journal of Computer Science and Technology, 2023)
Abstract In today s world many elements of our lives are being affected by software and for that we are in greater need of high-quality software The Unified Modeling Language UML is considered the de facto standard for object-oriented software model development UML class diagram plays an important role in the design and specification of software systems A class diagram provides a static description of system components
Keywords: formal methods; model verification; MDE; UML models; UML class diagrams